Thinking about Romney: Frame Building in a Battleground State in the 2012 Presidential Election. (March 2014) - Bedingfield, Sid; Anshari, Dien
Analyzing Ohio newspaper articles ( n = 466), this study investigates the framing of Mitt Romney in a key battleground state during the 2012 presidential election. Campaign officials and political journalists contend that attacks launched by President Obama in late spring defined Romney for the remainder of the campaign. Results suggest partial support for this claim by revealing increased use of negative media frames after the attacks began. Specifically, framing of Romney as a "vulture capitalist" increased significantly during the Obama frame-building effort. Findings offer theoretical insights into the concepts of frame building and "content bias" in media coverage of political campaigns.